Evaluación ultra estructural del Vitremer como material de interfase en las restauraciones con amalgama estudio in vivo - Falcon Guerrero, Brítto (2002)
The present investigation thought about in order to increasing the longevity of the restorations with amalgam without postoperative nuisances originated by micro filtrations; for that which has intended to evaluate the use of the Vitremer like interface material berween the amalgam and the dentarios tissues. 8 vital human teeth were used, suitable for exodoncia for reasons ortodoncicas, in those that he/she got ready Class cavities V in vestibular and lingual of oneself tooth; a total of 16 restorations, conformed in 2 groups being obtained: G-Control (n=8) with cavities of retentive walls that were only plugged with amalgam of high copper content. G-Prueba (n=8) with cavities of expulsive walls tried with a layer of previous Vitremer to the obturation with amalgam. After 2 weeks of clinical evolution, the teeth were extracted carefully without damaging the restorations; later on, previous cleaning of the bloody material dove in a solution of Karnosski and then they were continued with the conventional procedures of laboratory for the ultraestructural observation in the SEM to determine the presence of some degree of miero filtration in the regions oclusales and gingivales of the interface amalgam-tooth of both groups. Obviously, the control group showed different degrees of micro filtration in the mentioned regions of the referred interface, arriving a case until the wall pulpar The results were satisfactory in the group it proves, mosi of the cases didnt register micro filtrations in the region oclusal of the interface amalgam-tooth. However, in the interface in the region gingival, most of the cases showed micro total filtrations without arriving to the wall pulpar The statistical test of Chi Cuadrado (x) and the correction Yachts indicates that it is high1y significant the use of the Vitremer like interface material between the enamel and the amalgam, at a level of trust of 99.95 % (p<0.05).